Analysis of the development of decentralized international cooperation in the department of Arauca, Colombia (1991-2021) - Marín-Aranguren, Erli Margarita (2024)
In the year 2021, when this study began, the department of Arauca was positioned as one of the largest recipients of international cooperation resources in Colombia, due to the fact that the department presented problems that coincided with some of the issues prioritized by the country in the international cooperation agendas. This article analyzes the level of development achieved by decentralized international cooperation (CID) in the department of Arauca from 1991 to 2021, based on the inclusion of international cooperation issues in the Departmental Development Plan, the existence of legislation related to the formalization of CID and thecreation of coordination and management spaces at the departmental level.